2021
DOI: 10.1002/admi.202100763
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐Assisted Synthesis of Co3O4‐Based Electrocatalysts on Ni Foam Substrates for the Oxygen Evolution Reaction

Abstract: Electrocatalytic oxygen evolution reaction (OER) plays a key role in sustainable energy conversion and storage, but is severely hampered by the lack of efficient catalysts, whose development remains a critical and challenging issue. Herein, it is reported for the first time that pure and Fe2O3‐containing Co3O4‐based OER electrocatalysts are grown on highly porous Ni foams by plasma enhanced‐chemical vapor deposition and/or radiofrequency sputtering. Thanks to the inherent advantages of cold plasma synthesis ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…The charging voltage under light was related to the potential difference between the redox potential of Li + /Li and the CB of Ru/O V -MT/CC, which was theoretically lower than in the absence of light . As shown in Figure a, Ru/O V -MT/CC possessed lower charging potential and higher discharging potential than TiO 2 /CC, attributed to the combined effect of oxygen defects and plasma effect of noble metal nanoparticles in the Ru/O V -MT/CC material. , Besides, the Ru/O V -MT/CC cathode exhibited excellent photocatalytic stability. The charging potential of Ru/O V -MT/CC is significantly lower under illumination.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The charging voltage under light was related to the potential difference between the redox potential of Li + /Li and the CB of Ru/O V -MT/CC, which was theoretically lower than in the absence of light . As shown in Figure a, Ru/O V -MT/CC possessed lower charging potential and higher discharging potential than TiO 2 /CC, attributed to the combined effect of oxygen defects and plasma effect of noble metal nanoparticles in the Ru/O V -MT/CC material. , Besides, the Ru/O V -MT/CC cathode exhibited excellent photocatalytic stability. The charging potential of Ru/O V -MT/CC is significantly lower under illumination.…”
Section: Resultsmentioning
confidence: 95%
“…56 As shown in Figure 5a, Ru/O V -MT/CC possessed lower charging potential and higher discharging potential than TiO 2 /CC, attributed to the combined effect of oxygen defects and plasma effect of noble metal nanoparticles in the Ru/O V -MT/CC material. 62,63 Besides, the Ru/O V -MT/CC cathode exhibited excellent photocatalytic stability. The charging potential of Ru/O V -MT/CC is significantly lower under illumination.…”
Section: + °+ +mentioning
confidence: 98%
“…It is worth highlighting that both Ar- and air-treated samples revealed a remarkable current density improvement upon gCN functionalization, with either CoO, CoFe 2 O 4 , or CoPi. The anodic peaks between 1.35 and 1.5 V correspond to the MO → MO(OH) reaction usually occurring on the surface of Ni and Co oxide nanoparticles [ 27 ]. The higher peak intensity for NiF Ar and gCN Ar in comparison to the homologous gCN air and NiF air samples could be attributed to an enhanced Ni oxidation, related, in turn, to a less uniform substrate coverage by gCN in the case of Ar-treated samples.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, 40 mg of gCN and 10 mg of I 2 were dispersed into a beaker containing 50 mL of acetone and the resulting mixture was sonicated for 20 min. Then, a pre-cleaned [ 27 ] Ni foam substrate (cathode) and carbon paper (anode), connected to a DC generator, were immersed in the resulting suspension at a distance of 10 mm. For bare and functionalized gCN Ar -based materials, experimental parameters for the carbon nitride deposition (EPD conditions: 5 min/50 V) were optimized according to our recently published work [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 4,24 ] In addition, there are a number of different methods in the literature to regulate or improve the OER performance of the TM‐based nanostructured materials, such as morphological modulations in nanoscale, [ 25–27 ] crystal phase and facet engineering, [ 28,29 ] heteroatom doping, [ 30–32 ] compositional tuning, [ 33,34 ] hybrid or heterostructure formation, [ 35–37 ] amorphization, [ 38,39 ] defect/vacancy creation, [ 40,41 ] in situ transformations, [ 42 ] ion etching, [ 43,44 ] and plasma bombardment. [ 45–47 ] In particular, Yin et al demonstrated that intrinsic oxygen vacancies were highly beneficial to boost the OER performances of NiS 2 /CoS 2 nanowires [ 48 ] and Ir‐single atom decorated NiCo 2 O 4 nanosheets. [ 49 ] In contrast, high electrocatalytic activity with improved structural stability and conductivity was realized in Co‐doped NiS 2 nanosheets [ 50 ] and Cl‐doped LaCoO 3 hollow cubes.…”
Section: Introductionmentioning
confidence: 99%